h - D$1 (BHondt, Theo.s; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 24th European Conference on Object-Oriented Programming, ECOOP 2010, held in Maribor, Slovenia, in June 2010. The 24 revised full papers, presented together with one extended abstract were carefully reviewed and selected from a total of 108 submissions. The papers cover topics such as programming environments and tools, theoretical foundations of programming languages, formal methods, concurrency models in Java, empirical methods, type systems, language design and implementation, concurrency abstractions and experiences.
Keynote 1 -- Code Roots -- Programming Environments and Tools -- Detecting Missing Method Calls in Object-Oriented Software -- Debugging Model-Transformation Failures Using Dynamic Tainting -- Automatically Extracting Class Diagrams from Spreadsheets -- Theoretical Foundations of Programming Languages -- Adding Dynamic Types to C -- Essential AOP: The A Calculus -- The Essence of JavaScript -- Formal Methods -- Verifying Executable Object-Oriented Specifications with Separation Logic -- Verifying Generics and Delegates -- Recency Types for Analyzing Scripting Languages -- Concurrency Models in Java -- Correct Refactoring of Concurrent Java Code -- Programming Coordinated Behavior in Java -- JCoBox: Generalizing Active Objects to Concurrent Components -- Special Session: Empirical Methods -- Doubts about the Positive Impact of Static Type Systems on Programming Tasks in Single Developer Projects - An Empirical Study -- Type Systems -- A Type System for Data-Centric Synchronization -- Type-Safe Eventful Sessions in Java -- Capabilities for Uniqueness and Borrowing -- Keynote 2 -- Secret Valley -- Language Design and Implementation -- Embedding Languages without Breaking Tools -- Modules as Objects in Newspeak -- Inline Caching Meets Quickening -- Concurrency Abstractions -- Self-Replicating Objects for Multicore Platforms -- Reasoning about the Implementation of Concurrency Abstractions on x86-TSO -- Concurrent Abstract Predicates -- Experiences -- The Use of Overloading in Java Programs -- Falling Back on Executable Specifications -- Contract-Based Data Structure Repair Using Alloy.
Keywords: Computer science; Monoclonal antibodies; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Computer Communication Networks; Antibodies; Software Engineering/Programming and Operating Systems